Easy expectations and racial bias in economics instructor ratings - Jahangir, Junaid (My University, 2023)
The objective in this paper is to investigate the determinants of Economics instructor ratings in two universities in Edmonton based on the data available from the Rate My Professors (RMP) website. Based on random effects and multi-level regression analysis, it is found that instructor ratings are predominantly driven by difficulty level and grades received by students. Additionally, ethnic instructors receive significantly lower ratings, which is explained less by accent and more by race. If the reported difficulty level of a course and the grade received by a student capture “easy expectations” on the part of students in the RMP data, and if instructor ratings are driven by a combination of such "easy expectations" and racial bias on the part of students, then the case for using average instructor ratings for annual faculty evaluations is weakened.
Keywords: Rate My Professors; racial bias; course difficulty; teaching economics; teaching evaluations